Economic Analysis of Urban Upgrading Projects - Sotomayor, Maria Angélica (World Bank, Washington, DC, 2012)
This article shares some experiences with different techniques for estimating economic benefits and costs used by the Bank in appraising urban upgrading projects . The projects usually combine infrastructure investments and complementary activities to strengthen, build capacity and organize communities and government at different levels to ensure appropriate use of services provided and sustainability. Latin America's urban population jumped from 50 percent in 1960 to 75 percent in 2000 (108 and 389 million respectively), making it the most urbanized region in the world. Municipalities throughout Latin America are struggling to keep up with this growth, in difficult economic environments, making sustainable provision of basic services a huge challenge. The World Bank is working closely with national, regional and municipal governments in developing and financing urban upgrading projects.